PENGEMBANGAN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH ALIYAH AL-ITQON BOGOR - Fifih Alfi Wafiroh; Khoirul Agil Munawar (Program Studi Manajemen Pendidikan Islam, 2023)
This article discusses curriculum development in which many things must be considered in curriculum development, starting from understanding curriculum theories and concepts, curriculum development foundations and others related to the curriculum development process. The research method used is qualitative based on descriptive studies. The data collection techniques used were observation, interviews, and documentation studies carried out at MA Al Itqon. The results of this study are that the curriculum at MA Al Itqon uses the 2013 curriculum (K-13/Kurtilas) which has not yet implemented the independent learning curriculum, but in practice it is not entirely from the government because MA Al Itqon is a school that is in a boarding school environment. , which is equipped with Islamic boarding schools such as Tahsin, Qori/recitations, and Tahfidz. It is the pesantren program that is the advantage or uniqueness of this school, so the output of MA Al Itqon is that apart from being able to master general subjects it also masters other fields of religious knowledge. So the development of the curriculum at MA Al-Itqon is absolutely carried out dynamically to improve the quality of education in the future in accordance with the times..